Sociocultural Challenges in the Implementation of COVID-19 Public Health Measures: Results From a Qualitative Study in Punjab, Pakistan - Zakar, Rubeena; Yousaf, Farhan; Zakar, Muhammad Zakria; Fischer, Florian (Frontiers in Public Health, 2021)
Informed public health measures are crucial to curb the COVID-19 pandemic. The sociocultural context is important to understand the success or failure of implementing public health measures. This study explores the social and behavioral response to COVID-19 and unveils challenges in the implementation of related public health measures in Pakistan. Within this qualitative study, we conducted 34 telephonic/online in-depth interviews with youths, adults, elderly people, and healthcare professionals in the Punjab province of Pakistan. Framework analysis was used for data analysis. People's poor understanding about COVID-19 and the need for preventive measures were the major challenge in implementing public health preventive strategies. Study participants reported that the lockdown strategy increased poverty and unemployment. People's poor living conditions and living environment compelled them not to follow social distancing and restricting themselves to home. Additionally, an underdeveloped healthcare system was one of the major challenges for Pakistan. The culture of denial in Pakistan related to the epidemiology of COVID-19 was an important challenge within the implementation of public health preventive measures. It is extremely important that public health experts and social scientists work together to understand the contextual sociocultural factors which shape behaviors associated with the spread of a pandemic.